2005
DOI: 10.1677/erc.1.01072
|View full text |Cite
|
Sign up to set email alerts
|

Lack of deleterious effect on bone mineral density of long-term thyroxine suppressive therapy for differentiated thyroid carcinoma

Abstract: The effect of subclinical hyperthyroidism on bone mineral density is controversial and could be significant in patients with differentiated thyroid carcinoma who receive suppressive doses of levothyroxine (LT4). To ascertain whether prolonged treatment with LT4 to suppress thyrotropin had a deleterious effect on bone mineral density and/or calcium metabolism in patients thyroidectomized for differentiated thyroid cancer we have performed a cross-sectional study in a group of 88 women (meantSD age: 51t12 years)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 33 publications
6
46
2
1
Order By: Relevance
“…In our study, which involved a different patient group in many respects, we did not find a relationship between serum levels of FT 4 , TSH, and BMD, which may well be due to the fact that serum thyroid hormone and TSH levels have changed after the thyroidectomy. Indeed, despite the low serum TSH levels in most patients, overall BMD was within the normal age-corrected range, which is in line with a recent report in DTC patients (35).…”
Section: Discussionsupporting
confidence: 91%
“…In our study, which involved a different patient group in many respects, we did not find a relationship between serum levels of FT 4 , TSH, and BMD, which may well be due to the fact that serum thyroid hormone and TSH levels have changed after the thyroidectomy. Indeed, despite the low serum TSH levels in most patients, overall BMD was within the normal age-corrected range, which is in line with a recent report in DTC patients (35).…”
Section: Discussionsupporting
confidence: 91%
“…A modest inverse relationship has been found between lumbar spine and whole body BMD and LDL-cholesterol levels in post-menopausal women, and between BMD and LDL levels in pre-menopausal women [30]. This is consistent with another investigation, which reported an inverse correlation between serum cholesterol level and spine BMD parameters in 340 post-menopausal Danish women suppressive therapy on BMD, which is consistent with the results of a previous study that did not show an adverse effect of such therapy on bone integrity in women with DTC regardless of their estrogen status [38]. A systematic review of 21 studies of the effect of L-T4 therapy on BMD found that post-menopausal women with subclinical hyperthyroidism are at higher risk for developing osteoporosis, while men and premenopausal women are not [10].…”
Section: Proximal Femursupporting
confidence: 91%
“…Previous studies in patients with well-differentiated thyroid cancer receiving suppressive LT 4 therapy have shown conflicting results: no decrease in BMD at any age [5,6], bone loss only in postmenopausal women [17], or deleterious effects in both premenopausa and postmenopausal patients [18,19]. Systematic reviews of BMD in these patients have reported diverse conclusions [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…TSH-suppressive therapy has not been associated with decreased BMD in premenopausal women and men as evaluated by dual-energy X-ray absorptiometry (DXA) [3][4][5][6]. A study with young patients also did not suggest a detrimental effect of LT 4 on the attainment of peak bone mass [7].…”
Section: Introductionmentioning
confidence: 96%